Can Lumbar Stabilization Exercises Influence Synergy Pattern and Recruitment Time of Core Muscles in Chronic Mechanical Low Back Pain? Pre-Post Experimental Study (International Journal of Physiotherapy, 2023)
Background: Chronic low back pain (CLBP) is a condition in which there is active inhibition of recruitment of local stabilizers, causing the onset of deep abdominal muscle activity to be delayed. Change in Synergy Pattern (SP) and Recruitment Time (RT) of core muscles after treatment with Lumbar Stabilization Exercises (LSE) is lacking in the research literature. Objectives were to assess pre and post-intervention changes in SP and RT of Transversus Abdominis (TA), Rectus Abdominis (RA), Superficial Lumbar Multifidus (SMF), Longissimus (LG) bilaterally with surface Electromyography (sEMG) after treating with LSE.Methods: The trial was registered under the Clinical Trail Registry- India (CTRI/2022/09/046066). Thirty-seven participants (M=6, F=31) with CLBP aged 20-40 years were treated with LSE for 6 weeks, 3 alternate days per week. Participants were assessed at baseline for CLBP, post 3 and 6 weeks. Outcome measures were changed in SP measured in microvolts (μV) and RT in milliseconds (ms) of TA, RA, SMF, and LG bilaterally by sEMG and Pain that was assessed with NPRS should be out of bracket.Results: Repeated measures ANOVA was used as statistical analysis. sEMG revealed significant improvement in SP for TA and SMF bilaterally (p